Analysis of Low Noise Amplifier Design for 1 GHz IoT Water Monitoring System - Hamdani, Fadil; Susanto, Misfa; Heriansyah (International Journal of Aviation Science and Engineering - AVIA, 2024)
The Internet has greatly accelerated the development of machine-to-machine communication technologies, enabling the remote monitoring and control of water treatment processes. A key example of this is the Internet of Things (IoT)-based Water Quality Management (WQM) systems, which utilize wireless sensors to monitor environmental parameters in real-time. These sensors are connected to a central gateway that aggregates and transmits data, facilitating timely interventions when water quality deviates from standards. The use of wireless communication minimizes installation challenges and environmental disruption. However, signal attenuation, particularly in Ultra High Frequency (UHF) bands over water, presents a challenge due to factors like temperature variations, antenna height, and surface roughness. UHF signals, while favorable for IoT applications due to their high data throughput and low power consumption, face propagation limitations over water surfaces. Despite these challenges, UHF's ability to penetrate structures and support large networks makes it a viable choice for IoT in aquatic environments. This paper explores the design of low noise amplifiers (LNAs) to mitigate signal attenuation in IoT systems for WQM, with a focus on enhancing signal integrity while maintaining low power consumption. By optimizing LNAs, the study aims to address the unique communication challenges posed by water environments, ensuring reliable and efficient operation of WQM systems